Tuberculosis Infection In Women - Izhar Fitrah Ahmad; Edward Pandu Wiriansya; Andi Puspa Ratu; Sharen Kasim (CV. Inara, 2025)
The increasing number of deaths due to tuberculosis has triggered the national tuberculosis control program to continue to intensify, accelerate, extend and innovate the program.7A holistic approach must be taken in order to improve tuberculosis control and identify various risk factors associated with tuberculosis infection. The Global Tuberculosis Report 2018 reported that 90% of tuberculosis sufferers are adults and 10% are children (<15 years). Figure 1 shows tuberculosis sufferers worldwide, 64% are men and 36% are women with a ratio of 2:1. In Indonesia, data also shows that tuberculosis is more common in men than women. The high prevalence in men shows that the level of men accessing tuberculosis services is higher than women. Differences in social roles between men and women can also affect risk factors for access to health services. In women, access to tuberculosis treatment and prevention services is more difficult than in men. This is because family members do not want to pay for women's health services. Women's health in the family is considered less important than male family members. Tuberculosis problems also occur in vulnerable populations, namely pregnant women and women with tuberculosis-HIV. A fairly high mortality rate occurs in women with tuberculosis-HIV. In pregnant women, transmission of tuberculosis germs to the fetus occurs, so that the fetus can have latent tuberculosis. Understanding tuberculosis disease in women can help the target of eliminating tuberculosis by 2030. Gender equality and active participation of women in the planning, implementation, and health care processes can be an effective way to overcome the problems of difficulty in accessing tuberculosis services, stigma and discrimination, and various existing barriers.